The effects of thermal treatment of extract from Moringa Oleifera and variation on phytochemical distribution - Ala, Eddine Laib; Aref, kezzouz (university of eloued, 2018)
ABSTRACT This work was aimed to determine phytochemical composition and individual phenolic compound (HPLC) from Moringa Olfeira (leaves and vegetative shoots) and investigate their stability with heat treatment, by applying many varying temperatures which are 80 °C, 100 °C, 120°C and 140°C. The result before and after treatment found that the HPLC analysis show varying phytochemical composition. The Rutin acid decrease after applying any heat treatment and for Quercetin acid, the extreme quantity obtained at 140 °C. For Chlorogenic Acid, the high concentration obtained at 120°C for determine the quantity of phenolic compound using the Folin-Ciocalteu method show that before heat treatment the shoots have the extreme quantity, and after heat treatment this quantity was decrease. For FTIR analysis, the results confirmed that the hydroxyl group of phenolic compounds was decrease with. Further study anti-bactrian and anti-activity was investigated.الملخص تعرضنا في هاذا العمل الي استخلاص المركبات الفينولية من نبات المورينغا أولفيرا حيث كانت الاشكالية الاساسية هي معرفة تاثيرالمعالجة الحرارية على المركبات الفينولية و استقرارها, فقد عرضت العينات الى درجات حرارة متفاوة في القيمة وهي 80,100,120,140 درجة مئوية, وقد اظهرت النتايج باستخدام الة الاستشراب السائلي عالي الأداء قبل وبعد المعالجة الحرارية ان حمض الروتين يختفي بعد تعريض المستخلص لاي من درجات حرارة المذكورة, اما حمض الكروستين يوجد باعلى تركيز له في 140 درجة مئوية اما بالنسبة لحمض الكلوروجنيك وجد اعلى تركيز له عند التعريض لدرجة حرارة تساوي 120 درجة مىوية, ومن جهة اخرى باستخدام طريقة الفولان سيكالتو نجد قبل المعالجة الحرارية ان الاغصان تحتوي قيمة أعلى للمركبات الفنولية من الاوراق وبعد المعالجة الحرارية عند تطبيق درجة حرارة اقل من 140 يتناقص تركيزها. وقد تم التحقق من النتائج باستخدام الة الأشعة تحت الحمراء. مستقبلا يجب التحقق من اسقرار مضادات الاكسدة و مضادات البكتيريا.
Chemical Engineering
Keywords: Keyword Moringa Olfeira, phenolic compounds, heat treatments, HPLC analysis, stability, phytochemical composition, Folin-Ciocalteu.; الكلمات المفتاحية المركبات الفينولية, المورينغا أولفيرا, المعالجة الحرارية, استقرار المركبات الفينولية, لاستشراب السائلي عالي الأداء, التركيب النباتي , طريقة الفولان سيكالتو .